Uma introdução ao shabbat a partir da nova história política/An introduction to shabbat from new political history - Almeida, Fábio Py Murta de (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2015)
O objetivo do texto é discutir as experiências sociais e literárias projetadas pelo judaísmo decorrentes da influência do exílio Neobabilônico, percebendo como as diferentes comunidades judaicas exiladas entre 587-540 AEC encararam a vida sob o condicionamento desse império. A proposta que existe a partir da literatura da Bíblia hebraica é de uma sociedade que produz uma inovação no calendário, denominada de shabbat (o sábado). A indagação pontuada aqui quer perceber como esse fenômeno político-literário foi produzido no âmago da sociedade e da política do Oriente Antigo Próximo na cultura Neobabilônica. Abstract <span style="text-align: justify; font-size: 10pt; font-family: 'Bookman Old Style', serif; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-US">The aim of the text is to discuss the social and literary experiences designed by Judaism that arise from the influence of Neo-Babylonian exile, by realizing how different Jewish communities in exile between 587-540 BCE faced life under the conditioning of that empire. The proposal derived from the literature about the Hebrew Bible is that of a society that produces an innovation in the calendar, called Shabbat (the Sabbath). The quest punctuated here wants to understand how this political-literary phenomenon was produced at the core of Ancient Near East society and politics in the Neo-Babylonian culture.